2016
DOI: 10.3389/fnmol.2016.00033
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Axonal Responses to Injury: The Intersection between Signaling Pathways Involved in Axon Myelination and The Inhibition of Axon Regeneration

Abstract: Following spinal cord injury (SCI), a multitude of intrinsic and extrinsic factors adversely affect the gene programs that govern the expression of regeneration-associated genes (RAGs) and the production of a diversity of extracellular matrix molecules (ECM). Insufficient RAG expression in the injured neuron and the presence of inhibitory ECM at the lesion, leads to structural alterations in the axon that perturb the growth machinery, or form an extraneous barrier to axonal regeneration, respectively. Here, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 428 publications
(523 reference statements)
0
26
0
1
Order By: Relevance
“…Accumulating evidence suggests that the lack of regeneration capacity in the adult mammalian CNS is due to the presence of certain myelin-derived inhibitors, including the repulsive trio (Nogo-66, MAG and OMgp) (4,5). Inhibitory signaling is transduced via their receptors, NgR and PirB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence suggests that the lack of regeneration capacity in the adult mammalian CNS is due to the presence of certain myelin-derived inhibitors, including the repulsive trio (Nogo-66, MAG and OMgp) (4,5). Inhibitory signaling is transduced via their receptors, NgR and PirB.…”
Section: Discussionmentioning
confidence: 99%
“…CNS axons have regeneration capacity, but fail to regenerate predominantly due to environment obstacles that inhibit axonal regeneration after injury (3). It is reported that the inhibitory activity is closely associated with CNS myelin components and other molecules at the injury site (4). The three myelin-derived inhibitors, reticulon 4 (Nogo), myelinassociated glycoprotein (MAG) and oligodendrocyte myelin glycoprotein (OMgp), are potential inhibitors of axonal outgrowth in vitro; they interact with the lycosylphosphatidylinositol-anchored Nogo receptor (NgR) via their C-terminal 66-residue loops (Nogo-66) (5).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed the smallest cut may easily sever a nerve bundle in the skin leading to pain, axonal degeneration, and Schwann cells demyelination. In peripheral nerves, neuronal plasticity allows axons to grow back and the nerve bundle to regenerate [ 1 ]. However, elimination of myelin is critical as myelin proteins are known to inhibit axonal regeneration [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…In peripheral nerves, neuronal plasticity allows axons to grow back and the nerve bundle to regenerate [ 1 ]. However, elimination of myelin is critical as myelin proteins are known to inhibit axonal regeneration [ 1 ]. Finally, demyelinated Schwann cells then remyelinate axons to restore the full nerve function.…”
Section: Introductionmentioning
confidence: 99%
“…After damage to the peripheral nervous system, Schwann cells dedifferentiate into an immature cell type, proliferate to generate a larger population, and digest axon and myelin sheath debris to clear a regenerative path for subsequent axon regrowth Mirsky, 2008, 2016;Napoli et al, 2012). Schwann cells then migrate along and wrap around the regrown axons, establish a 1:1 ratio with axons, and undergo redifferentiation and myelination (Ness et al, 2013;Rao and Pearse, 2016). The phenotypes of Schwann cells can be modulated by various cellular and molecular factors, such as the neurotrophic factors nerve growth factor (Li et al, 2015) and brain-derived neurotrophic factor (Yi et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%